(untitled) (Journal of the College of Basic Education, 2025)
This study designed to help students to provide better answers in the examination, comprehend and understand texts in a more effective way. Moreover, it is useful for teachers to know about the reading strategies and being able to teach students how to use it, to plan lessons and apply effective methods of teaching reading for enhancing students’ vocabulary ability, reading comprehension performance and comprehending the text. The sample of the study consisted of ten students of sixth grade secondary school studying in Iraq. The objective of the study determine the metacognitive strategies that lead to an increase in reading comprehension performance and impact vocabulary ability to comprehend the text .In addition, this case study has been investigated whether they use the metacognitive strategies by using reading comprehension test and questionnaires. The data collected from (SPSS) packages the statistical package for social science. The data shown most students in this study are moderate -users of metacognitive awareness of reading strategies. Teaching the Metacognitive Awareness of Reading Strategies Inventory (MARSI) strategies will help students comprehend and understand texts in a more effective way and provide better answer in the examination, furthermore, will be useful for teacher to prepare their lessons.